PENGGUNAAN ANTIBIOTIK PROFILAKSIS DENGAN METODE GYSSENS PADA PASIEN BEDAH ORTOPEDI DI RUMAH SAKIT X PROVINSI BANTEN - Arrang, Jesica; Setiawan, Benny; Pramitaningastuti, Anastasia Setyopuspito (Jurnal Farmasi & Sains Indonesia, 2023)
Surgical wound infection (ILO) is one type of nosocomial infection that is commonly found in healthcare delivery in developing countries. Although most surgical patients receive prophylactic antibiotics, the incidence of ILO in orthopaedic surgery patients is still high. Therefore, it is necessary to evaluate the use of prophylactic antibiotics using the Gyssens method for orthopaedic surgery patients. This study is observational and retrospective data obtained from medical records of orthopedic surgery patients (Total Knee Replacement, Total Hip Replacement and Open Reduction, Internal Fixation) Hospital "X" in Banten Province for the period January 2022 - December 2022. Data were evaluated using the Gyssens method and presented descriptively. A total of 44 patient medical records that met the inclusion criteria. The results of the evaluation of prophylactic antibiotics using the Gyssens method showed that the appropriate use of prophylactic antibiotics was 93.18%, the time of administration of prophylactic antibiotics was 90.9%, the appropriate duration of antibiotic administration was 100%, and the use of antibiotics as follow-up therapy was carried out using Cefixime antibiotics as much as 22.73% and Cefadroxil as much as 2.27%, and the Gyssens Criteria for category 0 was 84.1%.